First results of LiDAR aided helicopter approaches during NATO DVE-Mitigation trials - Zimmermann, M.; Klasen, S.; König, C.; Lederle, A.; Wolfram, J.; Gestwa, M. (My University, 2017)
Landing a helicopter on unprepared sites can quickly become a challenging task in operational scenarios. Especially when environmental factors reduce the available visual cues for the pilot, the risk of disorientation increases. Motivated by avoiding accidents occurring in these Degraded Visual Environments (DVE), the NATO program for DVE-Mitigation (DVE-M) supports international efforts in the development of systems for enhanced situational awareness during DVE. A workgroup of the German Aerospace Center (DLR) and HENSOLDT Sensors GmbH participated at flight trials of the European NATO DVE-M campaign in Manching with DLRs highly modified research helicopter. The state of a system currently being under development was presented which combines eyes-out tunnel-in-the-sky symbology (SferiAssist®) with dynamic path updates based on a laser sensor. Details of four flights during the campaign in Manching performed in February 2017 are given and discussed in terms of a technical analysis and results of pilot evaluations